Visiting One's Native Country: The Risks of Nonadherence in HIV-Infected Sub-Saharan Migrants—ANRS VIHVO Study. (November 2013) - Abgrall, Sophie; Fugon, Lionel; Lélé, Nathalie; Carde, Estelle; Bentata, Michelle; Patey, Olivier; Khuong, Marie-Aude; Spire, Bruno; Carrieri, Patrizia; Bouchaud, Olivier
The aim of this study was to evaluate to what extent travel-related factors may cause adherence failure to antiretroviral therapy (ART) in otherwise adherent migrants when traveling back to Africa. HIV-infected sub-Saharian migrants living in France with a plasma HIV viral load < 200 copies/mL, with no change in ART for ≥3 months and who were about to visit their native country for between 2 weeks and 6 months were enrolled for the study. Patients completed a self-administered adherence questionnaire both at enrollment and during the week following their return to France. Adherence failure occurred in 23 (11.5%) of 200 patients. Negative perception about ART effectiveness (adjusted odds ratio = 4.3; 95% confidence interval = 1.3-13.7), unexpected traumatic events during their stay in their native country (7.8; 2.3-26.1), and a prolongation of their stay (5.2; 1.4-20.4) were independently associated with a higher likelihood of adherence failure. Owning/renting one's house in France (0.30; 0.10-0.96), singlehood (0.23; 0.05-1.00), and HIV status disclosure (0.19; 0.05-0.76) were correlates of sustained adherence during traveling.